Down syndrome is accompanied by significantly reduced cortical grey–white matter tissue contrast. Issue 10 (8th June 2018) - Bletsch, Anke; Mann, Caroline; Andrews, Derek S.; Daly, Eileen; Tan, Giles M. Y.; Murphy, Declan G. M.; Ecker, Christine
Abstract: Increased cortical thickness (CT) has been reported in Down syndrome (DS) during childhood and adolescence, but it remains unclear, which components of the neural architecture underpin these increases and if CT remains altered in adults. Among other factors, differences in CT measures could be driven by reduced tissue contrast between grey and white matter (GWC), which has been reported in neurodegenerative disorders, such as Alzheimer's disease. Using structural magnetic resonance imaging, we therefore examined differences in CT and GWC in 26 adults with DS, and 23 controls, to (1) examine between‐group differences in CT in adulthood, (2) establish whether DS is associated with significant reductions in GWC, and (3) determine the influence of GWC variability on between‐group differences in CT. As hypothesized, we observed that DS was accompanied by wide‐spread increases in CT, and significantly reduced GWC in several large clusters distributed across the cortex. Out of all vertices with a significant between‐group difference in CT, 38.50% also displayed a significant reduction in GWC. This percentage of overlap was also statistically significant and extremely unlikely to be obtained by chance ( p  = .0002). Differences in GWC thus seem to explain some, although not all, of the differences in CT observed in DS. In addition, our study is the first to extend previous in vivo reports of altered CT in DS during childhood and adolescence to older adults, implying that the regional pattern of neuroanatomical differences associated with DS remains stable across the lifespan.